2021
DOI: 10.1038/s41467-021-26337-1
|View full text |Cite
|
Sign up to set email alerts
|

A dual-reporter system for investigating and optimizing protein translation and folding in E. coli

Abstract: Strategies for investigating and optimizing the expression and folding of proteins for biotechnological and pharmaceutical purposes are in high demand. Here, we describe a dual-reporter biosensor system that simultaneously assesses in vivo protein translation and protein folding, thereby enabling rapid screening of mutant libraries. We have validated the dual-reporter system on five different proteins and find an excellent correlation between reporter signals and the levels of protein expression and solubility… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Several methods have already been developed for assaying in vivo protein stability with uorometric outputs [20][21][22][23] . However, these methods have not been tested with large, multidomain proteins such as PKSs.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have already been developed for assaying in vivo protein stability with uorometric outputs [20][21][22][23] . However, these methods have not been tested with large, multidomain proteins such as PKSs.…”
Section: Resultsmentioning
confidence: 99%
“…( 49). Such two-dimensional unfolding experiments have been used to study the stability of very stable designed proteins (Jacobs et al, 2016) and for the analyses of variants with widely different stabilities (Zutz et al, 2020). Examples of series of unfolding curves in both the temperature and denaturant dimension are shown in Fig.…”
Section: K As a Function Of Denaturant And Temperaturementioning
confidence: 99%
“…More quantitative analyses have been enabled by a thermodynamic model that considers doubly substituted protein variants to infer the effect of single amino acid substitutions on both protein-protein interaction and folding free energies 18,19 , which was later shown to match chemical unfolding stabilities well 20 . We have recently used a folding sensor based on a bacterial heat shock response 21 to select for variants with improved thermodynamic stability of an already stable protein 22 . In line with this, we have shown that single substitution effects may be obtained by analysing the results of a DMS experiment with many diverse multiple-substituted protein variants, and suggested a global multi-mutant analysis (GMMA) for this task 23 .…”
Section: Introductionmentioning
confidence: 99%